Cerebellar abscess caused by Listeria monocytogenes in a liver transplant patient. Issue 6 (23rd October 2013) - Choudhury, N.; Khan, A.B.; Tzvetanov, I.; Garcia‐Roca, R.; Oberholzer, J.; Benedetti, E.; Jeon, H.
Abstract Brain abscesses are a rare but serious complication and have been documented in transplant recipients. Aspergillus is by far the most frequent etiology of post‐transplant brain abscesses. Bacteria, apart from Nocardia, have a low association with brain abscesses in transplant recipients. We report herein the case of a 52‐year‐old man who had undergone orthotopic liver transplantation (OLT) for end‐stage liver disease and hepatocellular carcinoma secondary to chronic hepatitis, and who developed a cerebellar abscess (CA) from Listeria monocytogenes. Three months after transplantation, he presented with a 1‐week history of headache and vomiting. Computed tomography scan of the brain revealed a space‐occupying lesion in the right cerebellum, which was further confirmed by magnetic resonance imaging. Emergency surgery was planned because of pressure effect on the surrounding structures. The patient recovered smoothly from the surgery. To our knowledge, no reports of Listeria CA following OLT have been published in the English literature. This case shows that, although extremely rare, L. monocytogenes may cause CA in liver transplant recipients, and clinicians should be aware of this, so that prompt diagnosis and treatment can be instituted before serious brain damage can occur.